Answer:
- 1/64 (x+4)² (x-3) (x-4) = 0
Step-by-step explanation:
f(x) = a (x+4)²(x-3)(x-4) ... curve touch (-4,0) and not cross x axis
x=0 f(x) = -3
a (4)² * (-3) * (-4) = -3
a = - 1/64
- 1/64 (x+4)² (x-3) (x-4) = 0
Answer: The correct answer is
Step-by-step explanation:
Answer:
The inverse relation G^(-1) is not a function. Why not? Because the y value y = 3 is paired up with more than one x value (x = 5, x = 2). The inverse relation G^(-1) is the set shown below
{(3,5), (3,2), (4,6)}
All I've done is swap the (x,y) values for each ordered pair to form the inverse relation. As you can see, x = 3 leads to multiple y value outputs which is why this relation is not a function. So in short, the answer is choice C. To have the inverse relation be a function, each value in the original domain must map to exactly one value in the range only. However that doesn't happen as the domain values map to an overlapping y value (y = 3).
Answer:
288 cubic cm
Step-by-step explanation:
Volume of the pyramid = 1/3 * base area * height
Base area = 12 * 12
Base area - 144 sq. cm
Height = 6cm
Volume of the pyramid = 144 * 6/3
Volume of the pyramid = 144 * 2
Volume of the pyramid = 288 cubic cm